Computer-Based Experiment of Free Fall Movement to Improve the Graphical Literacy - Subali, B.; Rusdiana, D.; Firman, H.; Kaniawati, I.; Ellianawati, E. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2017)
The purpose of this study is to develop computer-based experiment of free fall movement to improve the graphical literacy of the Physics Education students. This study employed quasi-experimental design, particularly the pre-test and post-test control group design. The sample was 58 students of the first semester of Physics Education study program. They were divided into two groups, namely 38 students constituted an experimental group and 20 students constituted the control group. Both groups joined learning activities at laboratory and classrooms with the same topic which is the free fall movement. Computer-based learning models were used to design learning activities for the experimental group, while the control group used a traditional learning model with manual experiment with stopwatch and never use experiment tool of free fall movement. It was indicated in this study that the use of such learning model improved the graphical literacy capability better than the traditional learning, which covered ability to identify experimental variables, using the experimental tools, making a graph, formulating mathematical equation, making predictions on the basis of the graph.